Factors Influencing the Purchasing and Consumption of Unprescribed Pharmaceutical Products in Africa - Amoasi, Richard; Aboagye Agyeman, George (International Journal of Scientific Research and Management (IJSRM), 2023)
The proliferation of pharmaceutical shops, licensed chemical sellers with it attendant over-the-counter-drugs, the limited availability of health facilities and the vast difference between the cost of attending a hospital and the cost of buying known-drugs for use has necessitated the readily preference for majority of people in Africa particularly the middle and the low income groups to buy unprescribed medicines from pharmaceutical shops for use whenever they detect  a family member or a relative is not in a good state of health. The researchers sought to find out factors influencing majority in Africa buying medicines from medical shops for use without prescription, an issue destroying the youth as a result of abuse and in some cases putting the health of many in danger due to the little know how of the sales attendants in the medical shops. A sample size of 200 was used with a non-probability sampling method used to gather data obtained and a descriptive analysis used. The researchers identified the need for cost reduction for treatment to encourage hospital attendance and about a 200 bed capacity hospital per thousand of every household should be a policy in Africa. That a prescription should be inspected by both the pharmaceutical shops and other retailers prior to sale of pharmaceutical products or medicines. Keywords: pharmaceutical shops, medicines, self-medication, consumption, unprescribed